The role of family history as a risk factor for non-syndromic cleft lip and/or palate with multifactorial inheritance - Agung Sosiawan; Mala Kurniati; Coen Pramono Danudiningrat; Dian Agustin Wahjuningrum; Indra Mulyawan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Cleft lip with or without cleft palate (CL/P) is a facial growth ‘disorder that occurs during gestation and has multifactorial causes owing to both genetic and environmental factors. Several factors can increase the likelihood of CL/P, and one of them is family history. Differences in results obtained from studies conducted across several countries concerning family history as a risk factor for CL/P suggest there is no consensus on how the condition is inherited. Purpose: This study aims to review the literature on the role of family history as a risk factor contributing to the incidence of non-syndromic CL/P (NSCL/P). Review: This review discusses the etiology of CL/P and the risk factors influencing the incidence of CL/P. The review also examines the criteria for inheriting multifactorial disorders to calculate the risks involved should there be a recurrence of the condition based on family history. Conclusion: CL/P is a type of multifactorial disorder with unclear etiology. Therefore, it is important to investigate the risk factors stemming from family history (which play an important role) related to the recurrence risk. Additionally, there should be focus on increasing genetic education and offering counselling to parents and pregnant women.